COACHING DENGAN BOYATZIS INTENTIONAL CHANGE THEORY : MENINGKATKAN KUALITAS KEPEMIMPINAN KRISTEN DAN KARAKTER GURU - Saparso Saparso; Lim Fei Lien (Sekolah Tinggi Pariwisata Mataram, 2020)
This research is a school action research using the action research model proposed by Kemmis and McTaggart. Which discusses the problem of teacher attitudes and behavior at SDTK Harvest Berau. The purpose of this study was to determine the application of coaching with Boyatzis' Intentional Change Theory in building the quality of Christian leadership and the quality of teacher character in SDTK Harvest Berau. The research subjects were 8 teachers of the SDTK Harvest Berau. Data were obtained through questionnaires filled out by peers, self-assessments and researchers, which then the average score became an assessment of the quality of Christian leadership and the quality of teacher character. Data was also obtained through coaching notes carried out by researchers who were also the Principals. This research reveals that the quality of Christian leadership and teacher character qualities have increased through coaching with Boyatzis' Intentional Change Theory. 8 out of 8 teachers experienced an increase in the quality of Christian leadership and the quality of their character. So that teachers can apply Christian leadership qualities and character qualities more consistently in their lives.